Beyond Skill: The Paradoxical Link Between Financial Self-Efficacy and Anxiety in Indonesian University Students - Syamsuyurnita Syamsuyurnita; Faisal Rahman Dongoran; Reza Aditia (AL-ISHLAH: Jurnal Pendidikan, 2025)
Financial anxiety is common among university students and undermines academic and daily functioning. This study tested whether attitude toward money predicts financial self‑efficacy (FSE) and financial anxiety, whether FSE mediates that association, and whether the structural paths differ by gender. We used a cross‑sectional correlational design with 350 Indonesian university students selected via stratified random sampling. Attitude toward money was measured with the Money Attitude Scale, FSE with an adapted scale, and financial anxiety with the Financial Anxiety Scale. Hypotheses were examined using PLS‑SEM with 5,000 bootstraps and multi‑group analysis. Attitude toward money positively predicted FSE (β = 0.42, p .001), and FSE positively predicted financial anxiety (β = 0.18, p .001). The indirect effect of attitude toward money on financial anxiety via FSE was significant but small (β = 0.08, p = .01). No significant gender differences were detected. These results suggest that competence‑oriented financial education should be paired with stress‑management and risk‑appraisal components. For higher‑education policy and practice, campuses should integrate financial counseling with mental‑health services, deploy early‑warning systems for financial stress, and provide targeted supports such as emergency micro‑grants, peer money mentors, and flexible payment plans.